Respuesta :

Answer:

Step-by-step explanation:

First, open the parentheses!

6x^2 + 2x + 9x + 3 = 11x + 30

6x^2 + 11x + 3 = 11x + 30

Now solve this equation:

6x^2 + 3 = 30

x^2 = 2

x = √2

Sorry...I'm not sure if this is correct but hope it helps!

Answer:

[tex] x = \dfrac{3\sqrt{2}}{2}~~~or~~~x = -\dfrac{3\sqrt{2}}{2} [/tex]

Step-by-step explanation:

(2x + 3)(3x + 1) = 11x + 30

6x^2 + 2x + 9x + 3 = 11x + 30

6x^2 + 11x + 3 = 11x + 30

Subtract 11x from both sides. Subtract 3 from both sides.

6x^2 = 27

Divide both sides by 6

x^2 = 9/2

[tex] x = \sqrt{\frac{9}{2}}~~~or~~~x = -\sqrt{\frac{9}{2}} [/tex]

[tex] x = \frac{3}{\sqrt{2}}~~~or~~~x = -\frac{3}{\sqrt{2}} [/tex]

[tex] x = \dfrac{3\sqrt{2}}{2}~~~or~~~x = -\dfrac{3\sqrt{2}}{2} [/tex]